Imaging flow cytometry for multiparametric analysis of molecular mechanism involved in the cytotoxicity of human CD8+ T-cells - Wabnitz, Guido H.; Kirchgessner, Henning; Samstag, Yvonne (Journal of cellular biochemistry, 2017)
The clearance of tumors or virus infected cells is a crucial task of the immune system. Cytotoxic T-cells (CTLs) are able to detect and to kill such altered host cells. Given the recent success of checkpoint inhibitors for tumor therapy, it becomes more and more important to understand the biology of T-cell mediated target cell killing. Tests that allow analyzing the biology of CTLs are either based on flow cytometry or fluorescence microscopy. Thus, they either lack image-based information or have a poor statistical robustness. Therefore, we describe an approach to quantify CTL-mediated cytotoxicity using imaging flow cytometry. Using activated primary human cytotoxic T-cells as CTLs and P815 as target cells, we show that both the evaluation of target cell death and the biology of CTLs can be evaluated in parallel. This enables to gain information about CTL-mediated cytotoxicity in samples from patients important for translational medicine. J. Cell. Biochem. 118: 2528-2533, 2017. © 2017 Wiley Periodicals, Inc.
Gesehen am 11.07.2018